2019
DOI: 10.1021/acs.jpclett.9b01788
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorene and Black Phosphorus: The 31P NMR View

Abstract: This work aims at characterizing for the first time the 31 P spin interactions determining the Nuclear Magnetic Resonance (NMR) properties of solid black phosphorus (bP) and of its few-layer exfoliated (fl-bP) form. Indeed, the knowledge of these properties is still very poor, in spite of the great interest received by this layered phosphorus allotrope and its exfoliated 2D form, phosphorene. By combining Density Functional Theory (DFT) calculations and Solid State NMR experiments on suspensions of fl-bP nanof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…This will rely very much on the development of advanced microscopic characterization techniques such as HRTEM, AFM, or scanning tunneling microscope, in order to be able to monitor the reactions in real time (in situ) and to “see” the true chemical structures of the functional units attached onto BPNSs. Additional techniques such as solid NMR or 2D NMR or MS can be also employed to determine the chemical structures or to probe the interactions between functional units and BPNSs . Further support may come from theoretical calculations such as DFT, which will help to predict the chemistry, process, and mechanism .…”
Section: Discussionmentioning
confidence: 99%
“…This will rely very much on the development of advanced microscopic characterization techniques such as HRTEM, AFM, or scanning tunneling microscope, in order to be able to monitor the reactions in real time (in situ) and to “see” the true chemical structures of the functional units attached onto BPNSs. Additional techniques such as solid NMR or 2D NMR or MS can be also employed to determine the chemical structures or to probe the interactions between functional units and BPNSs . Further support may come from theoretical calculations such as DFT, which will help to predict the chemistry, process, and mechanism .…”
Section: Discussionmentioning
confidence: 99%
“…A special attention should be given to a number of papers dealing with the studies and discussion of pure solid‐state effects exemplified with the most recent contributions together with some older salient publications …”
Section: Computation Of 31p Nmr Chemical Shifts: Accuracy Factors Andmentioning
confidence: 99%
“…As an example, in the most recent publication Martini et al . combined DFT calculation with the solid‐state 31 P NMR experiment on the suspensions of nanoflakes and the solid black phosphorus, the latter shown in Figure .…”
Section: Computation Of 31p Nmr Chemical Shifts: Accuracy Factors Andmentioning
confidence: 99%
See 1 more Smart Citation
“…An interesting paper by Borsacchi et al identified and quantified the 31 P nuclear spin interactions determining the Nuclear Magnetic Resonance (NMR) properties of phosphorene and solid BP [18]. First, they acquired 31 P Magic Angle Spin (MAS) NMR spectra of samples of phosphorene of different nanoflake size and suspended in different solvents: dimethylsulfoxide (DMSO), tetrahydrofuran (THF), or methanol.…”
Section: Introductionmentioning
confidence: 99%